2019
DOI: 10.1242/dev.181180
|View full text |Cite
|
Sign up to set email alerts
|

The control of gene expression and cell identity by H3K9 trimethylation

Abstract: Histone 3 lysine 9 trimethylation (H3K9me3) is a conserved histone modification that is best known for its role in constitutive heterochromatin formation and the repression of repetitive DNA elements. More recently, it has become evident that H3K9me3 is also deposited at certain loci in a tissue-specific manner and plays important roles in regulating cell identity. Notably, H3K9me3 can repress genes encoding silencing factors, pointing to a fundamental principle of repressive chromatin auto-regulation. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 168 publications
3
100
2
Order By: Relevance
“…We also looked for genomic sites where gene expression levels might be affected by promoter DNA hypomethylation (at least 15% methylation change, 7CpGs), but found only one such locus ( Figure S3). Indeed, a number of Zbtb24-hypoDMRs are targets for H3K9me3 (Figure 3), which is associated with gene repression and a major silencing pathway in mESCs (Ninova et al 2019). Therefore, at these Zbtb24-hypoDMRs, persistent H3K9me3 could explain the absence of gene expression changes.…”
Section: Gene Expression Changes Upon Loss Of Zbtb24mentioning
confidence: 99%
“…We also looked for genomic sites where gene expression levels might be affected by promoter DNA hypomethylation (at least 15% methylation change, 7CpGs), but found only one such locus ( Figure S3). Indeed, a number of Zbtb24-hypoDMRs are targets for H3K9me3 (Figure 3), which is associated with gene repression and a major silencing pathway in mESCs (Ninova et al 2019). Therefore, at these Zbtb24-hypoDMRs, persistent H3K9me3 could explain the absence of gene expression changes.…”
Section: Gene Expression Changes Upon Loss Of Zbtb24mentioning
confidence: 99%
“…During SCNT-mediated nuclear reprogramming, H3K4me3 level decreases and H3K27me3 level increases (Cao et al, 2015;Xie et al, 2016;Zhai et al, 2018;Zhou et al, 2019). Another modification, H3K9me3, is catalyzed by suppressor of variegation 39H1/2 (Suv39H1/2) and removed by lysine demethylase (Kdm)4 (Kdm4a, Kdm4b, Kdm4d, and Kdm4e), and can alter chromatin conformation to inhibit gene expression (Ninova et al, 2019). H3K9me3 can be removed in donor somatic cells, but incomplete H3K9me3 demethylation in cloned embryos inhibits their development.…”
Section: Incomplete Epigenetic Reprogramming Underlies Low Cloning Efmentioning
confidence: 99%
“…First of all, H3K9me3 is not always associated with silencing. Studies in flies have shown that active genes that reside in constitutive heterochromatin are usually enriched in H3K9me3 across their bodies but not around the transcription start site, and loss of H3K9me3 results in transcriptional downregulation [29]. Moreover, Vakoc et al [30] showed that H3K9me3 and H3K9me2 occur, altogether with HP1γ, in the transcribed region of active genes in mammalian chromatin and are rapidly removed upon gene repression.…”
Section: Telomeres Are Euchromatic And/or Activementioning
confidence: 99%
“…Differences are probably due to the type and status of the cell, but also to the different techniques used. A hypothesis that could be put forward is that the epigenetic feature of telomeres is not spatially homogenous: the proximal part is heterochromatic, due to the vicinity of the subtelomere (in fact, H3K9me3 can spread in cis over several kilobases [29], whereas the distal part is marked by active histones and compacted by shelterins (and not repressive histones).…”
Section: Telomeres Are Euchromatic And/or Activementioning
confidence: 99%